Purification and structural analysis of volatile sesquiterpenes produced by Escherichia coli carrying unidentified terpene synthase genes from edible plants of the family Araliaceae. Issue 6 (3rd June 2018) - Shindo, Kazutoshi; Hattan, Jun-ichiro; Kato, Mariko; Sato, Miho; Ito, Tomoko; Shibuya, Yurika; Watanabe, Arisa; Sugiyama, Maki; Nakamura, Yuri; Misawa, Norihiko
Abstract: A simple method to purify volatile sesquiterpenes from recombinant Escherichia coli was developed using the cells that carried known sesquiterpene synthase ( Tps ) genes ZzZss 2 ( ZSS 2) and ZoTps 1. This method was applied for the purification and structural analyses of volatile sesquiterpenes produced by E. coli cells that carried unidentified Tps genes, which were isolated from the Aralia -genus edible plants belonging to the family Araliaceae . Recombinant cells carrying each Tps gene were cultured in the two-layer medium ( n -octane/TB medium), and volatile sesquiterpenes trapped in n -octane were purified through two-phase partition, silica gel column chromatography, and reversed-phase preparative high-performance liquid chromatography, if necessary. Further, their structures were confirmed by nuclear magnetic resonance, [α]D, and gas chromatography–mass spectrometry analyses. Herein, the products of E. coli cells that carried two Tps gene (named AcTps 1 and AcTps 2) in Araria cordata "Udo" and a Tps gene (named AeTps 1) in Aralia elata "Taranoki" were studied resulting in identifying functionalities of these cryptic Tps genes. Abstract: : Purification and structural analysis of volatile sesquiterpenes produced by Escherichia coli carrying unidentified terpene synthase genes from edible plants of the family Araliaceae .